The Influence of Different Digital Content Marketing on Consumer Engagement in The Tourism Sector - Khairani, Asmara; Fachira, Ira (International Journal of Social Science and Business, 2021)
Social media marketing and change in consumer behavior when traveling in the digital era present opportunities for the tourism sector. Aligned with these facts, digital content marketing becomes more important in improving consumer engagement through social media. Content marketing currently has shifted to a digital world known as digital content marketing. The more people view content on social media, the more it affects consumer engagement. Thus, a study is required to determine how social media marketing can help promote Indonesian locations., especially when Indonesia is trying to cope with many losses due to the pandemic. This study used content analysis to identify the differences between digital content marketing of the travel content by identifying 150 informative and persuasive content and analyzing consumer engagement on the social media platform Instagram. The results show that persuasive content has the most impact on consumer engagement. Also, this study can contribute to digital content marketing and consumer engagement concept literature in the tourism context.